Thermal performance analysis of staging effect of solar thermal absorber with cross design = Analisis prestasi haba kepada kesan berperingkat penyerap haba suria dengan reka bentuk bersilang - Abdul Razak, Amir; Abdul Majid, Zafri Azran; Ruslan, Mohd Hafidz; Sopian, Kamaruzzaman (Universiti Kebangsaan Malaysia (UKM), 2015)
The type and shape of solar thermal absorber materials will impact on the operating temperature and thermal energy storage effect of a solar air thermal collector. For a standard flat-plate design, energy gain can be increased by expanding the thermal absorber area along the collector plane, subject to area limitation. This paper focuses on the staging effect of a metal hollow square rod absorber of aluminium, stainless steel, and a combination of the two with a cross design, for the heat gain and temperature characteristics of a solar air collector. Experiments were carried out with three cross design set-ups, with 30 minutes of heating and cooling, phase, respectively, under 485 W/m2 solar irradiance value, and at a constant air speed at 0.38 m/s. One-set aluminium set-up delivered the highest output temperature of 41.8 °C, followed by two-sets aluminium and one aluminium set + one stainless steel set at 39.3 °C and 38.2°C, respectively. The lowest peak temperature is recorded on three sets of the aluminium absorber at 35 °C. The bi-metallic set-up performed better than the two aluminium set-up where each set-up obtained a temperature drop against heat gain gradient value of -0.4186 °C/W and -0.4917 °C/W, respectively. Results concluded that by increasing the number of sets, the volume and surface areas of the absorber material are also increased, and lead to a decrease in peak temperature output for each increase of sets.